A car of one’s own? A critical discourse analysis of the representation of women drivers in the Chinese-language news media - Sun, Ruixia (Technium Social Sciences Journal, 2024)
Nowadays it is commonplace for Chinese women to drive cars either as a means of transportation or for a job. Meanwhile, the varied voices as to women’s capacity to drive are heard in media reports. This article examines media representations of Chinese women drivers on the official news website Chinanews.com. News reports from 2012 to 2021 were collected, sorted in Nvivo 11, and analyzed under the guidance of van Leeuwen’s socio-semantic approach. The results of the analysis revealed three dominant discourses about women drivers: problematic discourse, commendable discourse, and victim discourse, in which categorisation strategy, nomination strategy and passivation strategy, along with the description of material actions and semiotic actions were employed. This study sheds light on the contradictory expectations placed on Chinese women and the perplexity felt by media regarding the social context of the increased mobility and freedom women have attained due to recent economic and social changes.